Eco-social glocalization? Egalitarian and elitist tendencies of the concept of urban governance - Brandtner, Christof (Momentum Quarterly, 2012)
Globalization involves a number of eco-social challenges for cities, which manifest themselves differently onthe local level. Through their enormous economic, political and demographic significance, cities play an extraordinarily important role in the reflexive relationship between the global and the local, which Robertson (1995) describes as glocalization. In consideration of the concept of urban governance, this paper discusses the effects of global dynamics on the local eco-social problem solving capacity in cities. The paper draws five conclusions: (1) Global development goes hand in hand with isomorphic change on the local level. (2) Institutional changes in cities have highlighted the importance of the concept of urban governance. (3) Urban governance has, first and foremost, elitist tendencies – the dogma of the entrepreneurial city has gained ground. (4) Urban governance, at the same time, brings along egalitarian tendencies – the inclusive city is the conceptual counterpart of the entrepreneurial city. (5) Eco-social glocalization is a matter of values.
Keywords: glocalization; cities; urban governance; institutional isomorphism; public management